Al-Tarbiyah Meaning in Al-Qurâan and its Implication in Learning and Commentary Education Major in Arabic FPBS UPI - Rosidin, Dedeng (EDUCARE, 2011)
ABSTRACT: In repertory Arabic, the term usually translated education with some vocabulary words, including âtarbiyahâ, study groups, âtadrisâ, âtadibâ, and âtahdibâ. The vocabulary of popular and commonly used to express terms of education. And the fifth is the vocabulary of the most popular and most widely used is âal-tarbiyahâ word. Semantic approach is commonly used to study more about this problem. This problem is studied from the aspect of language, how the term is used in a variety of lexical dictionary, and then how it is used in a variety of contexts in the Al-Quran. In the end result of the nature of meaning and pronunciation led to the concept of education in Islam. Based on the analysis and discussion of the meaning of the word âal-tarbiyahâ with its derivation, it is concluded that âal-tarbiyahâ is the process of development, maintenance, preservation, management, delivery of science, giving instructions, guidance, improvement, and sense of belonging for students both body, mind, soul, talent, potential, sense, on an ongoing basis, gradually, loving, caring, gentleness, good, wise, easily tolerated, thus forming the perfection of human nature, pleasure, glory, and live independently to achieve the pleasure of Allah SWT. The implications of the study results is that any interpretation of âal-tarbiyahâ, it should be explained by the semantic approach and perspective.KEY WORDS: Al-tarbiyah, semantic perspective, Al-Qurâan, teaching and learning process, and implication in Islamic education.About the Author: Dr. H. Dedeng Rosidin is a Lecturer at the Department of Arabic Language Education, Faculty of Arts and Language Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: anti.bandang@gmail.comHow to cite this article? Rosidin, Dedeng. (2011). âAl-Tarbiyah Meaning in Al-Qurâan and its Implication in Learning and Commentary Education Major in Arabic FPBS UPIâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.27-40. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 10, 2011); Revised (July 26, 2011); and Published (August 17, 2011).